Microtomographic view of external root resorption: an observational transversal study - Ângela Graciela Deliga Schröder,; Aline Xavier Ferraz,; Juliana Marodin Fauri Rotta,; Ana Julia Borkovski,; Cristiano Miranda de Araújo,; Vânia Portela Ditzel Westphalen, (Revista Sul-Brasileira de Odontologia, 2025)
This study investigated root resorption (RR), which can occur on the internal or external surfaces of the tooth, with difficulty in differential diagnosis using conventional radiography. Objective: To analyze external root resorption (ERR) through microtomography of ex vivo teeth. Material and methods: Two null hypotheses were tested: (1) the size and shape of natural root resorption are identical to those produced artificially; (2) the size and shape of natural root resorption differ from those produced artificially. Results: 126 teeth were scanned in high resolution, evaluated by calibrated radiologists, showing a higher incidence of RR in premolars (29.8%), followed by molars (27.7%), canines (23.4%), and incisors (19.1%), in relation to root thirds and location on the tooth surface. Conclusion: It was concluded that RR cavities exhibit a distinct architecture compared to those created by round burs, as observed in imaging modalities such as X-rays and cone beam computed tomography.